A Socio-Ecological Framework for Cancer Control in the Pacific: A Community Case Study of the US Affiliated Pacific Island Jurisdictions 1997–2017 - Palafox, Neal A.; Reichhardt, Martina; Taitano, John Ray; Nitta, Mavis; Garstang, Helentina; Riklon, Sheldon; Taulung, Livinson; Buenconsejo-Lum, Lee E. (Frontiers in Public Health, 2018)
The United States Affiliated Pacific Island Jurisdictions (USAPIJ) are politically linked to the United States (US) as US Territories (Guam, American Samoa), a US Commonwealth (Northern Mariana Islands), and as sovereign nations linked to the US through Compacts of Free Association (Federated States of Micronesia-FSM, Republic of the Marshall Islands-RMI, Republic of Palau). Cervical cancer incidence in the RMI is the highest in the world, mammography services are not available in the FSM and only Guam has on-island oncology services. Cancer risk factors such as obesity, tobacco, Hepatitis B are prevalent. Twelve years of nuclear testing in the RMI adds to the cancer burden. A community-based, multi-national coalition with multi-system external partners the Pacific Regional Cancer Control Partners (PRCP) was developed to address cancer prevention and control in the USAPIJ. Through the PRCP, local cancer coalitions, a regional cancer registry, 12 years of regional cancer control plans, and cancer prevention programs and research has been implemented. Methods: The PRCP is the subject of this community case study. The PRCP is analyzed through a socio-ecological theoretical framework to describe its typology, building blocks, and management. The respective roles and work of each partner and organization will be described and aligned with the levels of the socio-ecological framework. Results: The USAPIJs evolved a community-focused internal and external regional cancer prevention and control network over 20 years. The form and structure of the PRCP fit within a socio-ecological framework for cancer control. An adaptive management strategy has been used within the PRCP to manage its multi-national, multi-level, and multi-system partners. Conclusion: The PRCP has been able to advance cancer prevention and control programs with a community-centric model that functions in a multi-national, multi-cultural, low-resource, geographically dispersed environment over the last 20 years. The PRCP operates with a structure and management style that is consistent with a socio-ecological framework for cancer control. This case study provides a blueprint for the PRCP organizational structure and a mechanism for its function. The PRCP concept, a community-centric model for cancer control in multi-national resource-limited environments, may be scaled to similar global environments.